2021
DOI: 10.5194/isprs-annals-viii-4-w2-2021-99-2021
|View full text |Cite
|
Sign up to set email alerts
|

Citygml Application Domain Extension for 3d Strata Representations in the Smartkadaster System: Towards Beyond Cadastre Purpose in Malaysia

Abstract: Abstract. Recent advancements in 3D city modelling and emerging trends in implementing and realising Digital Twins motivate the Department of Survey and Mapping Malaysia (JUPEM) to develop and implement SmartKADASTER (SKiP) Phase 2. SmartKADASTER Phase I was a precursor to this system, and it primarily focused on applying two-dimensional (2D) spatial data for 3D spatial analysis. CityGML was used as the data model for various Levels of Detail (LoD) in this new initiative to represent city models across the Gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…LOD 0-4 of CityGML with its accuracy requirements [9]. This paper builds on previous publications [1,[10][11][12][13][14] on 3D geovisualisation in the SmartKADASTER Phase II environment. This paper aims to discuss the implications of automatically extruding the LoD1 height reference from the LoD0 height reference using only the classified ALS point cloud of a building.…”
mentioning
confidence: 87%
“…LOD 0-4 of CityGML with its accuracy requirements [9]. This paper builds on previous publications [1,[10][11][12][13][14] on 3D geovisualisation in the SmartKADASTER Phase II environment. This paper aims to discuss the implications of automatically extruding the LoD1 height reference from the LoD0 height reference using only the classified ALS point cloud of a building.…”
mentioning
confidence: 87%
“…Standards are usually considered vital, and extensive efforts have been undertaken to create mappings between various standards that relate to different aspects of physical objects. Examples from the built environment illustrate these concepts [Yu et al, 2022, Siew et al, 2021, Kumar et al, 2019, El-Mekawy and Östman, 2010, Sani et al, 2022, Saquicela et al, 2022.…”
Section: Interoperability Challengesmentioning
confidence: 99%
“…The third approach is extending existing data models to cover all data requirements. For example, some studies extended IFC (Atazadeh, Kalantari, Rajabifard, Ho, et al, 2017;Atazadeh, Kalantari, Rajabifard, Ho, & Champion, 2017) and CityGML (Halim et al, 2021;Nega & Coors, 2022;Saeidian et al, 2023aSaeidian et al, , 2023bSiew et al, 2021) to create a 3D integrated data model and reported this as a viable approach to develop a 3D integrated model. Although these studies developed a 3D integrated data environment, they only considered physical and legal data without incorporating survey data elements into the developed integrated model.…”
Section: Current S Tandards For Modelling Underg Round S U Rv E Y Datamentioning
confidence: 99%
“…In this regard, a range of CityGML Application Domain Extensions (ADEs) has been developed in several domains (Biljecki et al, 2018). Some studies have also investigated and suggested CityGML for land administration purposes (Halim et al, 2021;Nega & Coors, 2022;Saeidian et al, 2023aSaeidian et al, , 2023bSiew et al, 2021). However, this data model does not support cadastral survey elements in the current version (CityGML 3.0) and the studies also ignored defining these elements in the proposed…”
mentioning
confidence: 99%